The Effect of Using Culture Proficiency Computerized Wetland (CLDW)-based Modules on Protist Concepts on Generic Science Skills and Scientific Attitudes - Lumban Tobing, Fitri Ani; Putra, Aminuddin Prahatama; Utami, Nurul Hidayati (Vidya Karya, 2024)
Due to a lack of references, learning the concept of Protista requires learning materials to overcome students' difficulties. This includes identifying Protista species, learning about the characteristics of the Protista group, and classifying Protista. Culture Proficiency Computerized Wetland (CLDW) is a Learning The board Framework programming made to work with material conveyance during the growing experience. In addition to describing students' responses to CLDW-based modules, the research aims to examine the effect of CLDW-based modules on students' general science skills and scientific attitudes toward the Protista concept. This sort of examination utilizes the Semi Analysis strategy. This study's sample consisted of students in class X at SMAN 9 Banjarmasin, who were divided into one treatment and one control group. The Wilcoxon Signed Ranks Test and the SPSS 25 program were used to collect data on general scientific skills and scientific attitudes, which led to the following findings: From the exploration results, there is a huge impact of the utilization of CLDW-put together modules concerning the Protista idea on understudies' science conventional abilities with Asymp scores. Two-tailed sig. of 0.000-0.05 In the meantime, the scientific attitude data from this study show that students' scientific attitudes do not change significantly when CLDW-based modules are used, with scores at the Sig level (2-tailed) = 0.259 > 0.05. Furthermore, understudies' reactions to the utilization of CLDW-based modules were positive reactions in study hall learning, with a normal of 75% in the concur classification. According to the findings of this study, the module utilized by class X students at SMAN 9 Banjarmasin was approved and received a positive response.